MICROSTRIP ANTENNA WITH CIRCULAR POLARIZATION FOR RFID APPLICATIONS AT 2.4GHZ - Paz García, Nelson; Marante Rizo, Francisco; Paz Barrera, Steven Jesús (Telemática, 2020)
This paper proposes the design and simulation of an antenna with circular polarization for the 2.4 GHz band that can be used in radiofrequency identification or RFID (radiofrequency identification), using a microstrip feeding line and the grooved ground plane. Circular polarization is achieved through a lightning-shaped groove and optimized by automatically adjusting the proportions of that groove. The designed and simulated model has a good coupling, a gain of 3.49 dB and a bandwidth of 705 MHz for the desired frequency, reaching an efficiency of approximately 60%. It also has an axial bandwidth of 220 MHz, a sufficient range to meet its objective in RFID applications.